1c + 2p = 12.40
2c + 3p = 20.20
Equation 1 is in the correct format.
Equation 2 is in the correct format.
2c + 3p = 20.20
2c + 3p - 3p = 20.20 - 3p
2c = 20.20 - 3p
2c | |
2 |
= |
20.20 - 3p |
2 |
c = | 20.20 - 3p |
2 |
1(c) + 2p = 12.40
1 * ((20.20 - 3p)/2) + 2p = 12.40
((20.2 - 3p)/2) + 2p = 12.40
2 * (((20.2 - 3p)/2) + 2p = 12.40)
2 * (((20.2 - 3p)/2) + 2p = 12.40)
20.2 - 3p + 4p = 24.8
-3p + 4p = 24.8 - 20.2
1p = 4.6
1p | |
1 |
= |
4.6 |
1 |
p = | 4.6 |
1 |
p = 4.6
1c + 2(4.6) = 12.40
1c + 9.2 = 12.40
1c = 12.40 - 9.2
1c = 3.2
1c | |
1 |
= |
3.2 |
1 |
c = | 3.2 |
1 |
c = 3.2
Math is always fascinating! Have you noticed? On the path to discovering the ultimate mysteries of math, we move forward with small steps.